Co-solvent modified methylsulfonylmethane-based hybrid deep eutectic solvent electrolytes for high-voltage symmetric supercapacitors. (20th August 2022) - Huang, Ming-Kuen; Anuratha, Krishnan Shanmugam; Xiao, Yaoming; Chen, Yen-Pei; Lin, Jeng-Yu
Abstract: Deep eutectic solvents (DES) based electrolytes provide tremendous advantageous as green, safe, low-cost, nonflammability, and compositional tunability and thereby DES based electrolytes are more attracted towards energy storage and conversion devices. Herein, we illustrated the feasibility of using hybrid methylsulfonyl methane-based DES electrolytes with the introduction of water (W)/acetonitrile (AN) as co-solvents for activated carbon (AC) based symmetric supercapacitors (SC). Moreover, the molar ratio of co-solvents W/AN was systemically optimized for effectively improving the ionic conductivity and viscosity of hybrid DES electrolytes. Due to the excellent features of high ionic conductivity, low viscosity and improved flame retardant property, the optimized hybrid electrolyte enabled the 2.2 V AC-based symmetric SC and delivered an impressive specific capacitance of 31.2 F g −1 at a current density of 1 A g −1, and a high energy density of 21.4 Wh kg −1 at the power density of 1100 W kg −1 . More importantly, it also demonstrated an outstanding cycling stability evaluated by consecutive 20000 galvanostatic charge/discharge cycles and 120-h floating tests. Therefore, the W/AN-modified DES hybrid electrolytes will open up more opportunities for developing the low-cost and high-voltage electrolytes for energy storage applications.